Asia's competing multilateral initiatives: quality versus quantity. Issue 2 (4th March 2019) - Beeson, Mark
ABSTRACT: East Asia has many distinctive features that set it apart from other comparable regions, not least attitudes to regional development and cooperation. Despite a growing number of regional initiatives in East Asia, however, they are generally distinguished by their ineffectiveness. It is entirely possible that 'institutional balancing', like its more well-known power balancing counterpart, is designed not to facilitate but to prevent something from happening. The sort of 'multilateralism 1.0' developed by the Association of Southeast Asian Nations (ASEAN) has a lot to answer for in this regard: having established its own pattern of institutional effectiveness ASEAN's 'leadership' has caused it to be replicated under the new wave of 'multilateralism 2.0'. Consequently, I suggest that not only is China very comfortable with the idea of a rather feeble and ineffective institutional architecture, but the USA is also unlikely to do anything to change this picture, especially under a Trump administration that is highly skeptical about the efficacy of multilateral institutions at the best of times.